The Twilight of Sovereignty: How the Information Revolution is Transforming Our World - Wriston, Walter B. (Tufts Archival Research Center, 2008)
Twilight of Sovereignty: How the Information Revolution is Transforming our World is a compilation of speeches by Walter B. Wriston discussing the information technology.